Public acceptability of public health policy to improve population health: A population‐based survey. (24th April 2020) - Sharp, Catherine A.; Bellis, Mark A.; Hughes, Karen; Ford, Kat; Di Lemma, Lisa C. G.
Abstract: Background: For public health policies to be effective, it is critical that they are acceptable to the public as acceptance levels impact success rate. Objective: To explore public acceptance of public health statements and examine differences in acceptability across socio‐demographics, health behaviours (physical activity, diet, binge drinking and smoking), health status and well‐being. Method: A cross‐sectional survey was conducted with a nationally representative sample (N = 1001) using a random stratified sampling method. Face‐to‐face interviews were conducted at homes of residents in Wales aged 16+ years. Individuals reported whether they agreed, had no opinion, or disagreed with 12 public health statements. Results: More than half of the sample were supportive of 10 out of 12 statements. The three statements with the greatest support (>80% agreement) reflected the importance of: a safe and loving childhood to becoming a healthy adult, schools teaching about health, and healthier foods costing less. Individuals who engaged in unhealthy behaviours were less likely to agree with some of the statements (eg 39.8% of binge drinkers agreed alcohol adverts should be banned compared to 57.6% of those who never binge drink; P < .001). Conclusions: Findings show an appetite for public health policies among the majority of the public. The relationship between supporting policies and engaging in healthy behaviours suggests a feedback loop that is potentially capable of shifting both public opinion and the opportunities for policy intervention. If a nation becomes healthier, this could illicit greater support for stronger policies which could encourage more people to move in a healthier direction.